THE EFFECTS OF THE AQUATIC EXERCISES IN SEA, AS STRATEGY FOR THE IMPROVEMENT OF THE BALANCE IN SENIOR SENILE (Fiep Bulletin - online, 2015)
The objective of this study was to verify the difference among the balance in seniors submitted to aquatic exercises in sea, with the use of aquatic exercises in swimming pool, as much as the mechanisms proprioceptive for the process of information, with base in measurable processes, when they are considered the presented maladjustments, characteristic of his/her deficiency proprioceptive for the balance. Found in a technician-didactic-pedagogic program that it unchains incentives of functional complementation and quality of life, it intends to interfere in the condition of having destabilized, for a profile of balance body-mind, for an integration of the motive activity with the construction of the knowledge of his/her own body and better adjustment proprioceptive. The process that involves the problem of the mechanisms proprioceptive and of balance in disagreement with the senior's needs-65/75 years, it exhibits an approach between this senior one and the committed individual with this need, in this case, a professional of the area of the human behave, in what concerns to interventions solved defined, for the quantitative of inferences that the process predisposes. There is an estimate possibility that the balance lack in seniors is due to the decrease, or no acquisition of mechanisms movement and specific exercises for the maintenance of the balance during his/her social life, where it will be made a composition of these activities that you/they were presented in swimming pool (Cruz, 2000), for they be presented in sea. The senior is “fragile” in function of his/her muscular without structure no maintained in acceptable levels for the fitness/performance of a safe march, considering to be the middle in that he lives decisive and added difficulty for his/her fall, in function of mechanisms inadequate movement. Like this being, it should be looked for resources through of those mechanisms and/or of environment, to understand the intrinsic phenomena to the process, in the sense of contributing with intervening mensurations, indicating acceptable possibilities and manipulativas, accessible to the socioeconomic differences, in order to minimize the balance lack and to increase the propriocepção in seniors 65/75 years.
Keywords: Balance - Aquatic Exercises - Senior.